Shariah Governance for Islamic Capital Market - Robbi Maulana (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This research aims to identify and reconstruct sharia governance for sharia-based capital markets which aim to improve the economy, etc. The research method used is qualitative research. This research is a type of research whose findings are not obtained through statistical procedures or other forms of calculation. Qualitative research is based on the philosophy of post-positivism methods with natural object conditions, by placing the researcher as a small tool or instrument. The result of the discussion is that the Sharia Capital Market has proven its significant contribution to financial access, sustainable economic growth and investment by complying with sharia principles. Sharia financial instruments such as sukuk and sharia shares have opened the door to various parties who previously may have been reluctant to engage in conventional investments. By focusing on sectors that support sustainable economic development and social projects, the Islamic capital market provides diverse investment alternatives and supports economic inclusivity. Even though the sharia capital market offers great potential, there are still a number of problems in sharia governance that need to be overcome. Challenges in standardization, legal limitations, and lack of membership can affect the performance and incompetence of Islamic capital markets. By implementing measures such as harmonization of standards, increased transparency, and increased awareness, the Islamic capital market can strengthen its position as a driver of economic growth that is inclusive and in accordance with Sharia values.